01.27: Numerical analysis E‐stubs with four bolts per row. (13th September 2017) - Lopez, M.; Loureiro, A.; Gutierrez, R.; Reinosa, J. M.
ABSTRACT: The characterization of bolted steel joint behavior and properties have been matter of research for a number of years and all the accumulated knowledge has been compiled to a large extent in the currently available steel design codes like Eurocode 3. This design code uses the component method to evaluate the behavior of the steel joints. This paper will be focused in the study of E‐stub component with four bolts per row. This component appears in three dimensional joints with additional plates welded to the column flanges to attach beams in the minor axis. The E‐stub component is not covered by the formulation of Eurocode 3. Some works have been done in the component, formulations of stiffness and strength have been proposed in previous works but only for the case of two bolts per row. Because of that a 3D advanced finite element model has been developed in order to evaluate the influence of the 4 bolts per row and to compares the results of stiffness and strength with the case of 2 bolts per row.